Effect of plant harvesting on greenhouse gas emission from vertical subsurface flow constructed wetlands treating low-strength sewage - Siripoon Nutanong (2018)
© 2018, Desalination Publications. All rights reserved. The effect of plant harvesting patterns on CH4 and N2O fluxes from vertical flow constructed wetlands was investigated. Four identical constructed wetland units planted with Cyperus alternifolius were operated continuously for a period of 8 months during which plant harvesting periods were varied between 2, 4 and 8 months intervals. During the operation, CH4 and N2O fluxes were ranged between 1.73 and 3.63 mg C/m2 h and between 0.049 and 0.157 mg N/m2 H, respectively. Lowest CH4 fluxes were detected in the unit without harvesting during 8 months period whereas N2O fluxes were found lowest in the most frequent harvesting pattern (every 2 months). Analyses of dissolved oxygen and microbial community revealed different level of oxygen availability and greenhouse gas producing microbial population in the root zone between the treatment units.